(untitled) (Bibliouniversitas@ABRM.md, 2021)
The reference is a complicated process with many steps and strategies to search for information, being required for all types of libraries. However, the unit of measurement in the reference services is also the references. Bibliographic references can be presented in written and oral form. This method is an effective evaluation tool, which results in the improvement of the activity of reference librarians and with advantageous influences on the image in the society or community of the library. Key words: bibliographic references, reference librarians, library, reference services, information culture, traditional references, information resources, users, virtual references.